Effects of Soluble Lignocellulose Substances of Wood Particles on the Mechanical Properties of Lightweight Concrete - M. ALmusawi, Aqil; A. ALzaidi, Zaid; A. Qasim, Tamara (International Journal of Engineering and Technology, 2018)
Recent trends in lightweight concrete manufacturing have led to a proliferation of studies demonstrating that wood aggregates can be used to produce sustainable green concrete composites. However, wood particles contain soluble substances (saccharides), which have a significant effect on the setting time of Portland cement. To attain a better understanding of this, two types of wood were treated in boiling water. After the treatment process, the resulting water (â€œboiling water of woodâ€) was used to study its effect on the initial setting time of Portland cement. The mechanical properties and the density were also investigated for concrete mixtures consisting of 0, 5, 7.5, and 10% treated wood particles (weight replacement from coarse aggregate). As a result, the effect of the woodâ€™s soluble substances was determined and the optimum mix proportion was chosen for achieving the minimum nominal density and the best mechanical properties.Â Â